Hubungan Regulasi Diri dengan Perilaku Konsumtif Mahasiswa Prodi Bimbingan Konseling Fakultas Keguruan dan Ilmu Pendidikan Universitas Nusa Cendana - Pelohy, Yohanes Juanito Patty; Saba, Khetye Romelya; Abel, Rizky Mayesita Aryance (Prodi Bimbingan Konseling FKIP UNDANA, 2025)
Self-regulation is an individual's ability to accept and control themselves so that the goals they have set can be achieved. However, in reality there are still students who are unable to control themselves in fulfilling their needs and desires so that consumptive behavior among students is dominantly high. Consumptive behavior is a person's tendency to buy excessively and is based on desire. This research aims to determine (1) a description of the self-regulation of students in the Guidance and Counseling study program, Faculty of Teacher Training and Education, Nusa Cendana University, (2) a description of consumer behavior of students in the Guidance and Counseling study program, Faculty of Teacher Training and Education, Nusa Cendana University, (3) whether or not there is a relationship between self-regulation and consumer behavior of students in the Guidance and Counseling study program, Faculty of Teacher Training and Education, Nusa Cendana University. This research uses a quantitative approach with descriptive research type. The population in this research were students of the Guidance Counseling study program with a total of 470 students. The sampling technique was proportional stratified random sampling so that the sample consisted of 216 students. Data collection used a questionnaire with 50 items containing favorite and unfavorable items. The results of the research show: (1) the picture of student self-regulation is dominant in the high category, namely 53%, (2) the picture of student consumptive behavior is dominant in the low category, namely 48%, (3) there is a negative relationship between self-regulation and consumptive behavior in students with Pearson correlation -0.554 > 0.138. This research provides a contribution in the form of suggestions for students, the Guidance and Counseling study program, and future researchers regarding self-regulation and consumer behavior.